Asymmetric and long-run impact of political stability on consumption-based carbon dioxide emissions in Finland: Evidence from nonlinear and Fourier-based approaches - Kartal, Mustafa Tevfik; Depren, Serpil Kilic; Kirikkaleli, Dervis; Depren, Ozer; Khan, Uzma (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
The study investigates the asymmetric and long-run impact of political stability on consumption-based carbon dioxide (CCO2) emissions in Finland. In this context, the study examines the impact of political stability, economic growth, renewable energy consumption, and trade openness; includes quarterly data between 1990/Q1 and 2019/Q4, and applies nonlinear and Fourier-based approaches. The empirical outcomes reveal that (i) there is a long-run cointegration between CCO2 emissions and political stability as well as other controlling variables; (ii) positive changes in political stability have statistically significant impacts on CCO2 emissions, whereas negative shocks in political stability are not statistically significant. Also, positive shocks are more powerful than negative shocks; (iii) positive shocks in economic growth have significantly increasing impacts; (iv) positive and negative shocks in renewable energy have decreasing impacts on CCO2 emissions, while positive shocks are more powerful; (v) positive (negative) shocks in trade openness have decreasing (increasing) impacts on CCO(2 )emissions. Overall, the empirical results highlight the role of political stability on CCO(2 )emissions. Thus, consideration of political stability by policymakers of Finland in the policy development and implementation processes is highly recommended to achieve a carbon-neutrality target by 2035.
Keywords: Consumption-based CO2 emissions; Political stability; NARDL; Finland; ENVIRONMENTAL-QUALITY; Environmental Sciences & Ecology